2020
DOI: 10.1177/1747021820957135
|View full text |Cite
|
Sign up to set email alerts
|

Which cognitive functions subserve clustering and switching in category fluency? Generalisations from an extended set of semantic categories using linear mixed-effects modelling

Abstract: Clustering and switching are hypothesised to reflect the automatic and controlled components in category fluency, respectively, but how they are associated with cognitive functions has not been fully elucidated, due to several uncertainties. (1) The conventional scoring method that segregates responses by semantic categories could not optimally dissociate the automatic and controlled components. (2) The temporal structure of individual responses, as characterised by mean retrieval time (MRT) and mean switching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Additionally, it was hypothesized that FS switching performance would be predicted by language experience measures (language use questionnaire, or LUQ, metrics) as increased proficiency would lead to greater efficiency at implementing language control, resulting in less competition between the language control and semantic executive control levels. Finally, for BPWA, it was hypothesized that Raven’s Coloured Progressive Matrices (RCPM; Kertesz, 2006 ) scores, a measure of matrix reasoning ( Fong et al, 2020 ), would be predictive of performance on FS switching performance as better nonverbal cognitive function would lead to more controlled search processes as task demands increase.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was hypothesized that FS switching performance would be predicted by language experience measures (language use questionnaire, or LUQ, metrics) as increased proficiency would lead to greater efficiency at implementing language control, resulting in less competition between the language control and semantic executive control levels. Finally, for BPWA, it was hypothesized that Raven’s Coloured Progressive Matrices (RCPM; Kertesz, 2006 ) scores, a measure of matrix reasoning ( Fong et al, 2020 ), would be predictive of performance on FS switching performance as better nonverbal cognitive function would lead to more controlled search processes as task demands increase.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering and switching have been described as relatively automatic and controlled processes, respectively (Troyer & Moscovitch, 2006). Recent research shows that clustering and switching on SF are correlated with matrix reasoning and processing speed (Fong et al, 2020). Nonetheless, Vandek et al (2018) and Gabrić and Vandek (2020) found that clustering and switching on the tree, but not the animal task was associated with cognitive flexibility, indicating the existence of category specificities in clustering and switching.…”
Section: Clustering and Switching On Semantic Fluencymentioning
confidence: 99%
“…Despite its frequent use, the cognitive and specific linguistic correlates of SF remain mostly unclear. Although the presumed working memory and executive functioning components of both SF and letter fluency are often emphasized (Amunts et al, 2020), studies suggest that both general cognitive and specific linguistic processing subserve performance on verbal fluency (Fong et al, 2020;Stielow & Stenneken, 2017). Nonetheless, which linguistic (or lexical) processes subserve verbal fluency remains likewise unclear.…”
Section: Clustering and Switching On Semantic Fluencymentioning
confidence: 99%
“…Despite its frequent use, the cognitive and specific linguistic correlates of SF remain mostly unclear. Although the presumed working memory and executive functioning components of both SF and letter fluency are often emphasized (Amunts et al, 2020), studies suggest that both general cognitive and specific linguistic processing subserve performance on verbal fluency (Fong et al, 2020;Stielow & Stenneken, 2017). Nonetheless, which linguistic (or specifically semantic) processes subserve verbal fluency remains likewise unclear.…”
Section: Clustering and Switching On Semantic Fluencymentioning
confidence: 99%
“…Clustering and switching have been described as relatively automatic and controlled processes, respectively (Troyer & Moscovitch, 2006). Recent research shows that clustering and switching on SF are correlated with matrix reasoning (reflects the ability to apply knowledge in resolving a novel problem; Raven's Standard Progressive Matrices) and processing speed (Fong et al, 2020). Nonetheless, Vandek et al (2018) and Gabrić and Vandek (2020) found that clustering and switching on the tree, but not the animal task was associated with cognitive flexibility, indicating the existence of category specificities in clustering and switching.…”
Section: Clustering and Switching On Semantic Fluencymentioning
confidence: 99%